An exploratory analysis of the corporate identity of selected national government departments in South Africa - L Bezuidenhout L Bezuidenhout; CH van Heerden CH van Heerden (Communicare)
A communication task team appointed by the Government of South Africa in 1996 suggested that there should be one corporate identity for the government. A problem resulting from this suggestion was what this unitary corporate identity should reflect and which elements it should include. This article is based on a study into the viability of creating one corporate identity for all the South African government departments. Background is given for a government decision to create one corporate identity. The view that corporate identity consists of the integration between visual identity and behavioural identity and its possible application on the government departments of South Africa is discussed. The main finding of this study is that the current corporate identity of four selected government departments consists of corporate service and behaviour, dynamism and visual identity